As controvérsias a respeito da participação de Rosalind Franklin na construção do modelo da dupla hélice (Scientiae Studia, 2010)
In The double helix, James Watson narrated his version of the building of the DNA double-helix model, in which he indicates that Rosalind Franklin, a physicist specialized in X-Ray crystallography, developed empirical fundamental works to Watson and Crick's model construction. Watson's report gave rise to a historiographical problem: why Franklin, who disposes of the empirical data produced by herself, did not decipher the DNA molecular structure? Watson himself provides an answer, suggesting that Franklin had no theoretical inclination for a helicoidal representation of DNA, making strictly experimental work. This suggestion has received replies by historians, so that the historiographical problem subjacent to Watson's report maintains its actuality. Nevertheless, it is possible to obtain clues that, rather getting involved in the building of a new structure for DNA, Franklin was concerned with mapping all the aspects of the molecule. This article has two aims: showing that Franklin's line of defense adopted by some of her defenders in fact occasionally end up compromising Franklin, and presenting an outline of an alternative interpretation which, not attributing to Franklin the main goal of building a molecular structure for DNA, ends up giving her a much more comfortable role according to the historical point of view (which does not mean denying that she had the secondary goal of reaching a structure for DNA).